1997
DOI: 10.1021/bi961441r
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Resonance Energy Transfer Study of Shape Changes in Membrane-Bound Bovine Prothrombin and Meizothrombin

Abstract: Prothrombin activation to thrombin is a key control reaction in blood coagulation. During the process, prothrombin is sequentially cleaved at two peptide bonds (Arg323-Ile and Arg274-Thr) by factor X(a) to generate meizothrombin and then thrombin. Phosphatidylserine (PS)-containing membranes from platelets are believed to facilitate this two-step process. Using fluorescence energy transfer (FRET), we determined the distances of closest approach between a specifically located C-terminal fluorescein of a double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…It is therefore clear that the elongated APC protein binds to the membrane at one end and extends radially from the surface, a topographical motif that minimizes the phospholipid surface area occupied by the protein. Similar distances and conclusions have been obtained in previous studies with fVIIa (24), fIXa, (23), fXa (22,23), meizothrombin (25,26), and prothrombin (26). Thus, many of the proteolytic cleavages that effect and regulate hemostasis occur far above the membrane surface.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is therefore clear that the elongated APC protein binds to the membrane at one end and extends radially from the surface, a topographical motif that minimizes the phospholipid surface area occupied by the protein. Similar distances and conclusions have been obtained in previous studies with fVIIa (24), fIXa, (23), fXa (22,23), meizothrombin (25,26), and prothrombin (26). Thus, many of the proteolytic cleavages that effect and regulate hemostasis occur far above the membrane surface.…”
Section: Discussionsupporting
confidence: 87%
“…Our subsequent fluorescence energy transfer studies revealed that the active sites of factor Xa (fXa) (22,23), factor IXa (fIXa) (23), factor VIIa (fVIIa) (24), and meizothrombin (25), a prothombin derivative, are each located high above the membrane surface, thereby showing that the protease domain was located furthest from the bilayer in each case and confirming that the bound protein was oriented approximately perpendicularly to the plane of the membrane. The same conclusion was reached in another FRET study which showed that the protease domains of prothrombin and meizothrombin are both far above the surface, although in somewhat different locations (26). These spectroscopic results, obtained with membrane-bound proteins under near-physiological conditions, are completely compatible with the recently reported solid-state crystal structures of fIXa (27) and of fVIIa bound to a proteolyzed derivative of tissue factor (28).…”
supporting
confidence: 84%
“…Additionally, cleavage of II TM to yield an mIIa derivative resistant to further proteolytic processing or the addition of prothrombinase to cleavage resistant II QQ was accompanied by relatively minor changes in light scattering intensity (Fig. 1B), consistent with the equivalent size of prothrombin and mIIa as well as the established ability of these species to bind PCPS with similar affinity (36,37). Our findings indicate that thrombin formation, irrespective of further processing at Arg 155 , leads to a decrease in inferred size of the PCPS vesicle.…”
Section: Changes In Vesicle Size Associated With Prothrombinmentioning
confidence: 65%
“…These changes are associated with the formation of the substrate binding pocket and the oxyanion hole required for catalysis (11)(12)(13)(14)22). In the case of mIIa, these conformational changes could also be transmitted to the other domains that remain covalently attached (25). Because **Residues in the proteinase domain, numbered according to the homologous residues in chymotrypsinogen (22), are denoted by a C preceding the residue number.…”
Section: Discussionmentioning
confidence: 99%